1992
DOI: 10.1128/iai.60.7.2926-2935.1992
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Porphyromonas (Bacteroides) gingivalis fimbriae protects against periodontal destruction

Abstract: Adhesive fimbriae from Porphyromonas gingivalis are cell surface structures which may be important in the virulence of this oral pathogen and thus may serve as a critical or target antigen. Immunization with highly purified 43-kDa fimbrial protein protected against periodontal tissue destruction when tested in the P. gingivalis-infected gnotobiotic rat model. A similarly highly purified 75-kDa cell surface component did not provide protection. Heat-killed whole-cell and sonicated cell surface extracts which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 50 publications
1
85
1
1
Order By: Relevance
“…In searching for the appropriate antigen, we and others have examined a group of cell surface carbohydrates designated as K-antigens (12,32,59,60), lipopolysaccharides (10,26,43,58,70), and various proteins including fimbriae and fimbrillin (11,20,21,42,64) and the 53-kDa and 67-kDa cell surface proteins (30,71,72), hemagglutinin (37) and cysteine proteases referred to as gingipains or porphypain (5,13,22,34,40,45,48,55,56). Of the P. gingivalis components studied to date, the cysteine proteases have shown the most potential for use as vaccine antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In searching for the appropriate antigen, we and others have examined a group of cell surface carbohydrates designated as K-antigens (12,32,59,60), lipopolysaccharides (10,26,43,58,70), and various proteins including fimbriae and fimbrillin (11,20,21,42,64) and the 53-kDa and 67-kDa cell surface proteins (30,71,72), hemagglutinin (37) and cysteine proteases referred to as gingipains or porphypain (5,13,22,34,40,45,48,55,56). Of the P. gingivalis components studied to date, the cysteine proteases have shown the most potential for use as vaccine antigens.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that a vaccine directed against antigens of the infecting bacteria may be effective in preventing initiation and arresting the progresses of these diseases (7,20,22,23,40,46,66). Vaccine development presents four initial sets of problems.…”
mentioning
confidence: 99%
“…Oral immunization of mice with P. gingivalis fimbriae induces increased levels of fimbria-specific salivary IgA and serum IgG antibodies, while subcutaneous immunization of the fimbriae results in elevated serum IgM followed by IgG responses (30,31). In addition, immunization with highly purified P. gingivalis fimbriae was found to be protective against periodontal bone destruction in P. gingivalis-infected gnotobiotic rats (8). On the other hand, Chen et al (3) have reported that immunization with P. gingivalis lipopolysaccharide does not result in readily detectable antibody levels nor does it afford protection from a challenge infection with P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that P. gingivalis fimbriae are highly immunogenic and immunization with fimbriae purified from P. gingivalis 381 blocks the progression of experimental periodontal disease caused by the homologous strain (Evans et al, 1992). Although purified native fimbriae may be a useful immunogen for vaccination to block or reduce the severity of periodontitis, type I-rFimA vaccineinduced antibody responses may differ substantially from naturally acquired responses because type I-rFimA proteins do not fully represent the native structure (Shoji et al, 2010).…”
Section: Figmentioning
confidence: 99%